A unique radiation of marine littorinid snails in the freshwater streams of the Western Ghats of India: the genus Cremnoconchus W.T. Blanford, 1869 (Gastropoda: Littorinidae). (18th January 2013) - Reid, David G.; Aravind, Neelavara Ananthram; Madhyastha, Neelavara Ananthram
<x xml:space="preserve">Abstract</x> The caenogastropod family Littorinidae is almost exclusively marine, but a unique freshwater genus, Cremnoconchus, is known from India. Its members are restricted to montane streams on the western escarpment of the Western Ghats, at altitudes between 300 and 1400 m. Four species and several varieties were described in the 19th century, but no taxonomic study has been carried out for over 120 years and the last anatomical report was in 1935. Nevertheless, they are of unusual evolutionary interest and also of conservation concern as a genus endemic to the Western Ghats biodiversity hotspot. Based on anatomical study of newly collected material and examination of historical and type specimens, we present a systematic revision of Cremnoconchus, illustrating shells, radulae, and reproductive anatomy. The very large eggs, invaginated penial filament, and calcified operculum are unique among Littorinidae. Three valid, described species (C. syhadrensis, C. conicus, C. canaliculatus) are recognized in the northern Western Ghats in Maharashtra state, where all can occasionally be found sympatrically. We describe an additional six new species from the central Western Ghats in a small area (linear distance 80 km) of Karnataka state, over 500 km south of the previously known range of the genus. Here the species each appear to be restricted to a single drainage system. Because of their highly restricted distribution and fragile habitat, this radiation of nine species is judged to be endangered. © 2013 The Linnean Society of London